A study of the relationship between exercise, dietary factors and blood cholesterol levels in a group of active young men - Zammit, Ingrid Vivienne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- Universiteit van Stellenbosch, 1969.